2022
DOI: 10.3390/pathogens12010017
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Batch Normalized Convolution Approach for Improving COVID-19 Detection from Chest X-ray Images

Abstract: Pre-trained machine learning models have recently been widely used to detect COVID-19 automatically from X-ray images. Although these models can selectively retrain their layers for the desired task, the output remains biased due to the massive number of pre-trained weights and parameters. This paper proposes a novel batch normalized convolutional neural network (BNCNN) model to identify COVID-19 cases from chest X-ray images in binary and multi-class frameworks with a dual aim to extract salient features that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The reduction of imaging case volume was justified by the absolute need to protect healthcare personnel and patients from infectious risk. For avoiding this issues technology and science plaied a significant part in particular innovative tools as teleradiology and artificial intelligence (AI) were implemented and for a better care for affected patients all over the world ( 20 , 21 ). AI is made to act and think like a human brain, automating many tasks by imitating its thought processes.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of imaging case volume was justified by the absolute need to protect healthcare personnel and patients from infectious risk. For avoiding this issues technology and science plaied a significant part in particular innovative tools as teleradiology and artificial intelligence (AI) were implemented and for a better care for affected patients all over the world ( 20 , 21 ). AI is made to act and think like a human brain, automating many tasks by imitating its thought processes.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Waisy et al [43] proposed the COVID-CheXNet system, a hybrid deep-learning architecture that successfully diagnosed COVID-19 patients with an accuracy rate of 99.99%. As for binary and three-class classifications, Al-Shourbaji et al [44] proposed a batch-normalized convolutional neural network (BNCNN) model and used other pre-trained models such as VGG-16, VGG-19, Inception-V3, and ResNet-50 to detect COVID-19 and other lung diseases from the CXR images. Their results showed that the BNCNN model outperformed the pretrained models, with accuracies of 99.27% for the binary class and 96.84% for three-class classifications, respectively.…”
Section: Comparison To Related Work In the Literaturementioning
confidence: 99%
“…Moreover, elective imaging services were stopped to decrease the virus’s transmission ( 8 ). This decision had a significant impact on hospitals’ level of financial revenue.…”
Section: Introductionmentioning
confidence: 99%